Transcriptome analysis of basic fibroblast growth factor treated stem cells isolated from human exfoliated deciduous teeth. Issue 6 (June 2020) - Nowwarote, Nunthawan; Manokawinchoke, Jeeranan; Kanjana, Kiattipan; Fournier, Benjamin P.J.; Sukarawan, Waleerat; Osathanon, Thanaphum
Abstract: Background: Basic fibroblast growth factor (bFGF) regulates cell proliferation, migration, and differentiation in various cell types. The aim of the present study was to determine the bFGF target genes in stem cells isolated from human exfoliated deciduous teeth (SHEDs). Methods: Cells were isolated from pulp tissue obtained from exfoliated deciduous teeth. Mesenchymal stem cell surface markers and the differentiation potential toward adipogenic and neurogenic lineages were characterized. The bFGF-treated SHED transcriptome was examined using a high throughput RNA sequencing technique. The mRNA and protein expression of selected genes were evaluated using real-time polymerase chain reaction and immunofluorescence staining, respectively. Cell cycle analysis was performed by flow cytometry. The colony forming unit number was also examined. Results: The isolated cells expressed CD44, CD90, CD105, but not CD45. The upregulation of adipogenic and neurogenic marker genes was observed after culturing cells in the appropriate induction medium. Transcriptome analysis of the bFGF treated cells revealed that the upregulated genes were in the cell cycle related pathways, while the downregulated genes were in the extracellular matrix related pathways. Correspondingly, bFGF induced MKI6 7 mRNA expression and Ki67 protein expression. Furthermore, bFGF treatment significantly decreased the G0/G1, but increased the G2/M, population in SHEDs. Colony formation was markedly increased in the bFGF treated group and was attenuated by pretreating the cells with FGFR or PI3K inhibitors. Conclusion: bFGF controls cell cycle progression in SHEDs. Thus, it can be used to amplify cell number to obtain the amount of cells required for regenerative treatments. Abstract : Cell biology; Bioinformatics; Transcriptomics; Biomedical engineering; Molecular biology; Regenerative medicine; Basic fibroblast growth factor; Transcriptome; RNA sequencing; Stem cells isolated from human exfoliated deciduous teeth